Model Pembelajaran Problem Based Learning dalam Meningkatkan Pencapaian dan Keaktifan Para Pelajar Kelas VIII SMPN 172 Jakarta - Afriandini Aisyah; Desy Safitri; Nandi Kurniawan (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
The objective of this research is to assess the effectiveness of the Problem Based Learning (PBL) model in enhancing students achievement and active participation in Grade VIII at SMP Negeri 172 Jakarta in the Social Studies subject. This research is based on the importance of preparing students for the challenges of the 21st century, which require critical, analytical, and creative thinking skills. The method used is Classroom Action Research (CAR) with 35 students from class VIII-3 as participants. There are two cycles in this study, consisting of planning, implementation, observation, and reflection phases. In the first cycle, although PBL was implemented, only 43% of students scored above the Minimum Mastery Criteria (KKM) of 80, with an average score of 71. Additionally, their activeness in asking questions, answering, expressing opinions, and solving problems was still low. Reflection indicated that students needed time to adapt to PBL and required more motivation from the teacher. In the second cycle, after improvements were made, there was a significant increase. As many as 89% of students scored above the KKM of 80, with an average score of 88. Student activeness also increased with more active participation in class activities. This shows that students better understood and adapted to the PBL model and received better encouragement from the teacher. In conclusion, the implementation of the PBL model is effective in improving students achievement and active participation in the Social Studies subject at SMP Negeri 172 Jakarta. This is evidenced by the significant increase in students average scores and their active participation in learning. The PBL model is capable of stimulating students critical, analytical, and creative thinking skills, as well as enhancing their engagement in learning, creating a more conducive and efficient environment for achieving educational goals.